2003
DOI: 10.1111/j.1530-0277.2003.tb02715.x
|View full text |Cite
|
Sign up to set email alerts
|

NPY leu7pro and Alcohol Dependence in Finnish and Swedish Populations

Abstract: Pro7 does not seem to be associated with a diagnosis of alcoholism in Caucasian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 38 publications
1
16
1
3
Order By: Relevance
“…In humans, linkage to the chromosomal region containing the NPY gene has been demonstrated 47, and there have been associations of NPY variation with both alcohol consumption 40 and dependence 48, 49. Other studies, however, have failed to replicate this association 5052. Of note, our present study did not find any effects of rh NPY −1002T>G on alcohol consumption in normally reared animals, even following repeated alcohol exposure.…”
Section: Commentcontrasting
confidence: 44%
“…In humans, linkage to the chromosomal region containing the NPY gene has been demonstrated 47, and there have been associations of NPY variation with both alcohol consumption 40 and dependence 48, 49. Other studies, however, have failed to replicate this association 5052. Of note, our present study did not find any effects of rh NPY −1002T>G on alcohol consumption in normally reared animals, even following repeated alcohol exposure.…”
Section: Commentcontrasting
confidence: 44%
“…Another report showed that European American men with alcoholism have a 5-5.5% Pro7 allele frequency, whereas the corresponding figure in nonalcoholic men was only 2% [155]. Subsequent studies, however, could not replicate this association [156]. A positive association between a novel polymorphism located in the 5 0 region of the NPY gene and alcohol dependence was recently identified in a Nordic population, but replication of their findings is yet to be published [157 ].…”
Section: Neuropeptide Y and Neuropeptide Y Receptorsmentioning
confidence: 99%
“…The lower frequency of the pro7 allele observed in Finnish type 2 alcoholic individuals indicated the protective effect of this allele against alcohol dependence [25]. In contrast, several studies have failed to show a significant association between the pro7 allele and alcohol dependence [34] or alcohol withdrawal symptoms [35]. A significant elevation in the T allele of NPY -C5671T was observed in Japanese alcohol-dependent subjects during withdrawal, but this significance vanished after Bonferroni correction [36].…”
Section: Discussionmentioning
confidence: 99%